Prophylaxis for blood-borne diseases during the London 7/7 mass casualty terrorist bombing: a review and the role of bioethics. Issue 5 (23rd February 2016) - Edwards, Dafydd S; Barnett-Vanes, A; Narayan, N; Patel, H D L
Abstract : The suicide bombings in London on 7 July 2005 resulted in a mass casualty situation. Over 50% of casualties were treated at the Royal London Hospital where clinicians witnessed large numbers of severely injured patients. In some casualties human biological foreign material was found embedded in the soft tissue originating from the suicide bombers or other casualties. This had the potential of placing individuals at risk of transmission of blood-borne diseases. Advances in the fields of medicine and biology have led to increased survivorship in the context of trauma and mass casualty incidents. This has resulted in the emergence of ethical scenarios surrounding patient management. A systematic review of the literature of the 7/7 bombings, and suicide bombings reported globally, where biological implantation is noted, was performed to examine the medicolegal issues arising during such attack. Twelve casualties with human tissue implanted were recorded in the 7/7 bombings. While all patients at risk were given prophylaxis based on recommendations by the Health Protection Agency, several ethical considerations surfaced as a result. In this paper, we compare the sequence of events and the management process of the victims of the 7/7 bombings and the evidence-based research regarding blood-borne infection transmission. Furthermore, it explores the ethical dilemmas, experienced by the senior author on 7/7, surrounding prophylaxis for blood-borne diseases and protocols to avoid confusion over best practice in future bombing incidents.